UI flat design and skeuomorphism mediation with neumorphism (material design) - Andreas James Darmawan; Elizabeth Jessica Sentani; Adela Carera; Clarissa Fidelya Gerungan; Dina Agustina Lestari Gultom (Universitas Indraprasta PGRI, 2025)
This study discusses the mediation between Skeuomorphism and Flat Design through the Neumorphism or Material Design approach in interface design or user interface (UI). Skeuomorphism UI is known to present user nostalgia with realistic visuals that maintain the correlation of real objects, but often loads the performance of handheld devices. In contrast, Flat Design UI offers memory efficiency through minimalist images with flat color blocks, but tends to disappoint and confuse users. Neumorphism UI emerges as a solution that combines the advantages of both, creating visuals that still resemble real objects but are lighter, presenting a minimalist realistic feel. This study uses a qualitative method with a descriptive approach, data collection through purposive sampling, literature studies and interface design observations. The results of the study are expected to contribute as learning materials in introducing, using, and creating better interface designs, both in terms of aesthetics and functionality. By understanding the role of Neumorphism UI as a mediator between visual nostalgia and efficiency of use, interface designers are expected to be able to present an optimal, innovative, and relevant user experience (UX) with technological developments.